(untitled) (Stato, Chiese e pluralismo confessionale, 2024)
Religious minorities in Italy between the treaty system and common law ABSTRACT: This paper examines the status of religious minorities in Italian law, which is based on a double channel: common law (State and regional laws) and agreements between the Government and some religious denominations approved by act of Parliament. It also examines the main theses that have emerged in the most recent doctrinal debate, the orientations of constitutional case-law and some reform proposals on the matter. In the end the author highlights the pros and cons of the current legal system and its substantial correspondence to the original constitutional design. SOMMARIO: 1. Sul concetto di minoranze religiose: attualità e aspetti critici - 2. Minoranze religiose e migrazioni - 3. Le minoranze religiose nel diritto internazionale - 4. Le confessioni religiose nel sistema costituzionale italiano - 5. La condizione giuridica delle confessioni religiose tra sistema pattizio e diritto comune - 5.1. Le confessioni religiose riconosciute - 5.2. Le confessioni religiose con intesa - 6. Dalle intese al sistema pattizio - 7. Il sistema pattizio nel più recente dibattito dottrinale - 8. Il sistema pattizio nella giurisprudenza costituzionale - 9. Proposte di riforma - 10. Status delle confessioni religiose e diritto comune - 11. Osservazioni conclusive.